Situation in Bilbao : inter-departmental correspondence - McDonald, Florence
016a-0017-001 I.C.3. TRADES UNION CONGRESS GENERAL COUNCIL. INTER-DEPARTMENTAL CORRESPONDENCE. From F. McDonald To Mr. E. Bevin. Department Secretary's Date 21st June, 1937. SUBJECT. Situation in Bilbao. Sir Walter is up at the National Federation of Building Trades Operatives' Conference to-day. He asked me to show you this for your information. He thought if enquiries were made while he is away, you could then say that you know he has been in contact with the Foreign Office about the Bilbao situation. 292/946/16a/19